Near-complete phase transfer of single-wall carbon nanotubes by covalent functionalization - Kakade, Bhalchandra A.; Patil, Sanjay; Sathe, Bhaskar; Gokhale, Suresh; Pillai, Vijayamohanan (Journal of Chemical Sciences, 2008)
We describe here an efficient phase transfer of single wall carbon nanotubes (SWNTs) from aqueous to non-aqueous media using a unique amide functionalization route, where water soluble SWNTs (2.6 mg/mL) are effectively transferred to solvents like chloroform, toluene and CS(2). A maximum of 30 wt% of oxygenated groups have been generated on the side walls by rapid microwave treatment, leading to a solubility of more than 2.6 mg/mL in water. Approximate surface amine coverage of 50% has been accomplished after oxalyl chloride treatment as inferred from thermogravimetry and X-ray photoelectron spectroscopy by controlling several key parameters associated with the extent of functionalization including purity of the sample, temperature and time.
International Conference on Molecules and Materials - New Directions, Bangalore, INDIA, DEC 04, 2008
Keywords: Carbon nanotubes; microscopy; Microwave; Nanostructures; solubility of SWNTs

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)